Implementing Aksin Wijaya’s Maqāṣidĭ Interpretation of Q.S. Al-Nisaʾ (4): 1, 3, and 11 on Gender Relations - Musthafa, Hilman; A'an Khunaifi, Muhammad; Nabilah Fatihatul Firjah, Putri (Universitas Islam Negeri Madura, 2026)
This study examines Aksin Wijaya's thoughts on maqāṣidĭ interpretation as a new approach in the study of the Qur'an that emphasizes the search for spiritual-contextual meaning. Although the concept of maqāṣidĭ has been practiced by classical mufassirs, maqāṣidĭ tafsir has only recently developed theoretically. Aksin Wijaya uses a combination of three approaches: tafsir taḥlilĭ to find textual meaning, tafsir nuzūlĭ and objective hermeneutics to explore context and moral-ideals, and philosophical hermeneutics to find spiritual-contextual meaning. The method used in this paper is library research with descriptive data processing analysis. The result of the research shows the relevance of meaning in the contemporary context. The theory application implies that this day, there found urgent need for review and reconsideration of inheritance matters while still paying attention to strict sharia rules so that the distribution remains balanced but does not deviate from the essence of sharia.